Dose–response of rPMS for upper Limb hemiparesis after stroke. Issue 24 (12th June 2020) - Kinoshita, Shoji; Ikeda, Kumi; Yasuno, Shinji; Takahashi, Sho; Yamada, Naoki; Okuyama, Yumi; Sasaki, Nobuyuki; Hada, Takuya; Kuriyama, Chiaki; Suzuki, Shin; Hama, Midori; Ozaki, Naoto; et al.
Abstract: Introduction: Repetitive peripheral magnetic stimulation (rPMS) therapy is an innovative and minimally invasive neurorehabilitative technique and has been shown to facilitate neural plasticity. However, there is at present no research that clarifies the dose–response of rPMS therapy on the recovery of upper limb hemiparesis after stroke. This trial aims to clarify the dose–response of rPMS therapy combined with intensive occupational therapy (OT) for chronic stroke patients with moderate to severe upper limb hemiparesis. Methods and analysis: This multicenter, prospective, assessor-blinded, randomized controlled study with 3 parallel groups will be conducted from January 20, 2020 to September 30, 2022. Fifty patients will be randomly assigned in a ratio of 1:2:2 to the control group, the group receiving daily 2400 pulses of rPMS, or the group receiving daily 4800 pulses of rPMS, respectively. From the day after admission (Day 1), rPMS therapy and intensive OT will be initiated. The primary outcome is the change in the motor function of the affected upper extremity (Fugl-Meyer Assessment) between the time of admission (Day 0) and the day after 2 weeks of treatment (Day 14). Secondary outcomes will include the changes in spasticity, active range of motion, motor evoked potential, and activity of daily living. Ethics and dissemination: The study was approved by the Jikei University Certified Review Board for all institutions (reference number: JKI19–020). Results of the primary and secondary outcomes will be published in a peer-reviewed journal and presented at international congresses. The results will also be disseminated to patients. Trial registration number: jRCTs032190191.